Moral education and autonomy in children's education: what thinks the teachers - Adelaide Alves Dias (Psicologia: Reflexão e Crítica, 2005)
This paper aims to analyze autonomy and moral education concepts held by children's female teachers and to relate these concepts to the development of pedagogic practices in children's education. Anchored in the theoretical framework of moral education as construction, it presupposes that the way female teachers conceive these phenomena may influence their educational actions, orientating sometimes their own practices. 15 children's teachers from 8 public nursery schools in Niterói – RJ, have taken part in this research. The interviews have shown, through qualitative procedures of categorization and content analysis, that the majority of female teachers exposed abstract and individualized concepts of autonomy and moral education. They have also shown that these concepts make up the basis of the educational proposals to promote teachers' autonomy, thus pointing to the need to reflect upon the foundations of moral education which is supposedly autonomous, taking into account the infant's specificities.